Clinical features of double infection with tick-borne encephalitis and Lyme borreliosis transmitted by tick bite. Issue 12 (5th June 2006) - Logina, I; Krumina, A; Karelis, G; Elsone, L; Viksna, L; Rozentale, B; Donaghy, M
Abstract : Background: In Latvia and other endemic regions, a single tick bite has the potential to transmit both tick-borne encephalitis (TBE) and Lyme borreliosis. Objective: To analyse both the clinical features and differential diagnosis of combined tick-borne infection with TBE and Lyme borreliosis, in 51 patients with serological evidence, of whom 69% had tick bites. Results: Biphasic fever suggestive of TBE occurred in 55% of the patients. Meningitis occurred in 92%, with painful radicular symptoms in 39%. Muscle weakness occurred in 41%; in 29% the flaccid paralysis was compatible with TBE. Only two patients presented with the bulbar palsy typical of TBE. Typical Lyme borreliosis facial palsy occurred in three patients. Typical TBE oculomotor disturbances occurred in two. Other features typical of Lyme borreliosis detected in our patients were distal peripheral neuropathy (n = 4), arthralgia (n = 9), local erythema 1–12 days after tick bite (n = 7) and erythema chronicum migrans (n = 1). Echocardiogram abnormalities occurred in 15. Conclusions: Patients with double infection with TBE and Lyme borreliosis fell into three main clinical groups: febrile illness, 3 (6%); meningitis, 15 (30%); central or peripheral neurological deficit (meningoencephalitis, meningomyelitis, meningoradiculitis and polyradiculoneuritis), 33 (65%). Systemic features pointing to Lyme borreliosis were found in 25 patients (49%); immunoglobulin (Ig)M antibodies to borreliosis were present in 18 of them. The clinical occurrence of both Lyme borreliosis and TBE vary after exposure to tick bite, and the neurological manifestations of each disorder vary widely, with considerable overlap. This observational study provides no evidence that co-infection produces unusual manifestations due to unpredicted interaction between the two diseases. Patients with tick exposure presenting with acute neurological symptoms in areas endemic for both Lyme borreliosis and TBE should be investigated for both conditions. The threshold for simultaneous treatment of both conditions should be low, given the possibility of co-occurrence and the difficulty in ascribing individual neurological manifestations to one condition or the other.